2012
DOI: 10.1111/j.1365-2885.2012.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the predictive performance of a pharmacokinetic model for propofol in Japanese macaques (Macaca fuscata fuscata)

Abstract: Propofol is a short-acting intravenous anesthetic used for induction/maintenance anesthesia. The objective of this study was to assess a population pharmacokinetic (PPK) model for Japanese macaques during a step-down infusion of propofol. Five male Japanese macaques were immobilized with ketamine (10 mg/kg) and atropine (0.02 mg/kg). A bolus dose of propofol (5 mg/kg) was administrated intravenously (360 mg/kg/h) followed by step-down infusion at 40 mg/kg/h for 10 min, 20 mg/kg/h for 10 min, and then 15 mg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The difference between measured and predicted Cps deviated more in the early phase compared to later phases. This observation is consistent with previous reports that the measured propofol Cps can differ greatly from predicted Cps during the first few minutes of administration in humans 22 and also in Japanese macaques 23,24 and common marmosets 25 . This is probably because these models make the incorrect assumption of immediate mixing of administered drugs within the central compartment.…”
Section: Discussionsupporting
confidence: 93%
“…The difference between measured and predicted Cps deviated more in the early phase compared to later phases. This observation is consistent with previous reports that the measured propofol Cps can differ greatly from predicted Cps during the first few minutes of administration in humans 22 and also in Japanese macaques 23,24 and common marmosets 25 . This is probably because these models make the incorrect assumption of immediate mixing of administered drugs within the central compartment.…”
Section: Discussionsupporting
confidence: 93%
“…The final model was better than the model established with all Cp data because MDPE and MDAPE were better due to large variations of Cps at 2 min after administration. It was reported that Cps of propofol within a few min after starting administration varied greatly in human medicine and Japanese macaque studies (Masui et al, 2009; Miyabe‐Nishiwaki et al 2010, 2013). It might cause the variation of Cps due to reduction of flow back from the caudal circulation to systemic circulation in marmosets as well.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the pharmacokinetic model achieved stable prediction of propofol plasma concentrations in Japanese macaques [22].…”
Section: Discussionmentioning
confidence: 99%
“…To check kinetic nonlinearity, the first experiments were performed on 10 rabbits, which received 3 different single doses of phenytoin (11,22, 44 mg/kg). The period between administration of doses was 10 days.…”
Section: Methodsmentioning
confidence: 99%